HUBUNGAN ANTARA INDEKS MASSA TUBUH (IMT) DENGAN KADAR LEMAK TOTAL (Studi Kasus Pada Mahasiswa Kedokteran Undip) - Zega Yudama Archilona; Heri-Nugroho Heri-Nugroho; Niken Puruhita (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background  : Total body fat’s content is one of many indicators that affects  weight gain and body mass index. Total body fat’s content is important because it can lead to various diseases such as type 2 diabetes mellitus, hypertension, and dyslipidemia. Body mass index (BMI) can describe a person's nutritional status. Measurement of both BMI and total body fat’s content should use the recommended tools such as the use of CT scans and MRI, but these tools are very expensive and impractical. This study used a tool called Tanita that used BIA method because it is more practical and cheaper in the measurement of BMI and total body fat’s content.Objectives : Knowing whether there is a relationship between BMI and total body fat’s  content in Undip medical students.Methods : This study was an observational study with cross sectional analytic study. The data that was taken in this study included BMI, total body fat’s, smoking, sex, physical activity, habits of consumption of fatty foods, and alcohol consumption. statistical test with chi-square correlation test (x2).Results :  There were significant correlation between body mass index and the total body fat’s content (p = 0.000). The other confounding variables were found no significant correlation (p> 0.05).Conclusions : The meaningful and positive correlation of body mass index and total body fat’s content do exist.